Business Communication Strategy In Improving Customer Confidence Regarding The Quality of Drinking Water Companies For Regional Drinking Water - Kurniawan, Dea; Waskito, Budhi; Verawati, Noning (Interaction Communication Studies Journal, 2025)
This study aims to analyze and design a business communication strategy to increase customer trust in the drinking water quality provided by PDAM Kota Bandar Lampung, particularly in the Teluk Betung Barat area. Despite having access to piped water, many customers still prefer bottled water (AMDK), indicating a lack of confidence in PDAM’s water for direct consumption. Using a qualitative descriptive method with a post-positivist approach, data were collected through interviews, observations, and documentation. Informants included PDAM officials and customers. The results show that communication factors—such as limited public education, lack of transparency, and inconsistent messaging—contribute to customer distrust. SWOT analysis was used to identify internal and external factors that affect communication performance. The study recommends strategic improvements through transparent, community-based communication, increased use of social media, and proactive crisis communication. An integrated communication strategy is essential to rebuild trust and reduce public dependence on bottled drinking water.